"The Fe Effect": A review unveiling the critical roles of Fe in enhancing OER activity of Ni and Co based catalysts. (February 2021) - Anantharaj, Sengeni; Kundu, Subrata; Noda, Suguru
Abstract: Electrocatalytic oxygen evolution reaction (OER) catalyzed by non-precious metals and their compounds in alkaline medium is an attractive area of energy research for the generation of hydrogen from water. The 3d transition metals, particularly, Ni and Co show better OER activity than others in alkaline medium. Ni and Co based oxygen-evolving catalysts (OECs) experience an enormous enhancement in the OER activity either by incidental or intentional Fe doping/incorporation. To account for this, different roles of Fe that it exerts when incorporated into these OECs are reported to be responsible. Unfortunately, the conclusions drawn in many related studies are often contradictory to one another. Important contradictory conclusions are: 1) a few studies claim Fe is the active site and Ni/Co are inactive while other studies claim Ni/Co and Fe act together in OER, 2) a few studies claim Fe 3+ stays unoxidized while a few shows evidence for the existence of Fe 4+, and 3) a few studies suggest Fe 3+ is the faster site in Ni/Co OEC matrices for OER but fail to explain similar effects observed with other OER matrices. Many critical experimental and theoretical investigations have been made recently to reveal this magical Fe effect and the results of those studies are coherently presented here with critical discussion. This review is presented as it is inevitable to know the critical roles of Fe effect in Ni/Co based OECs to succeed in energy efficient hydrogen generation in alkaline medium. Graphical Abstract: ga1 OER activity of Ni and Co based OEC experiences humongous enhancement when Fe3+ ions are accidentally or knowingly incorporated into them. The roles that Fe3+ ions perform in enhancing the OER activities of these catalysts are comprehensively discussed here in this review. Highlights: OER enhancing effect of Fe in Ni and Co based OER catalysts is discussed in detail. Mechanisms by which Fe effects such an enhancement is detailed. Seminal discoveries of "The Fe Effect" are critically analyzed. Challenges and opportunities that are available for furthering research in the field are highlighted.